Kommunale bewegungsbezogene Gesundheitsförderung in Deutschland - Lea Dippon; Natalie Helsper; Simone Kohler; Philipp Weber; Alfred Rütten; Klaus Pfeifer; Leonie Birkholz; Jana Semrau (German Journal of Exercise and Sport Research, 2024)
Zusammenfassung Ansätze der kommunalen bewegungsbezogenen Gesundheitsförderung (kbG) werden empfohlen, um körperlicher Inaktivität in der Bevölkerung entgegenzuwirken. Der vorliegende Artikel hat zum einen das Ziel, eine systematische Übersicht zur kbG in Deutschland darzustellen. Zum anderen sollen in diesem Bereich Good-Practice-Projekte identifiziert werden, die als Orientierungsrahmen für die Umsetzung und Verbreitung von kbG genutzt werden können. Im ersten Schritt wurden Projekte über eine Suche in 4 wissenschaftlichen Datenbanken sowie 21 Projektdatenbanken identifiziert und Daten zu „Bundesland“, „Berücksichtigung gesundheitlicher Chancengleichheit“ und „Umsetzung im städtischen oder ländlichen Raum“ extrahiert. Zudem wurden eingeschlossene Projekte in verschiedene Ansätze im Setting Kommune unterteilt. Im nächsten Schritt wurden Projekte mit einer dokumentierten Prozess- und/oder Ergebnisevaluation anhand von Qualitätskriterien in den Bereichen Konzipierung, Implementierung und Evaluation bewertet. Projekte, die mindestens 50 % der Qualitätskriterien erfüllten, wurden als Good-Pratice-Projekte ausgewählt. Insgesamt wurden 240 Projekte der kbG erfasst. Im ländlichen Raum wurden primär umweltbezogene Ansätze und im städtischen Raum vermehrt Mehrkomponentenansätze sowie Angebote und Veranstaltungen umgesetzt. 45 Projekte wiesen eine ausreichende Dokumentation der Prozess- und/oder Ergebnisevaluation auf, wovon 17 Projekte als Good-Practice identifiziert wurden. Optimierungspotenzial besteht bei der Adressierung von gesundheitlicher Chancengleichheit, einer aktiven Beteiligung von Menschen in schwierigen Lebenslagen über den gesamten Projektzyklus sowie der Implementierung von Mehrkomponentenansätzen. Dies erfordert Förderprogramme, die strukturbildende Good-Practice-Projekte ermöglichen und insbesondere deprivierte Kommunen erreichen. Ein von Akteur:innen aus Wissenschaft, Praxis und Politik gemeinsam verabschiedeter Standard zur Anwendung der Qualitätskriterien und einer damit einhergehenden Legitimation für die Bezeichnung als Good-Practice könnte einen Mehrwert für die strategische Weiterentwicklung der kbG in Deutschland bieten.

Short-Term Response of Deep-Water Benthic Megafauna to Installation of a Pipeline Over a Depth Gradient on the Angolan Slope - Virginia Biede; Andrew R. Gates; Simone Pfeifer; Jane E. Collins; Carmen Santos; Daniel O. B. Jones (Frontiers in Marine Science, 2022)
Large structures are introduced into deep-water marine environments by several industrial activities, including hydrocarbon exploitation. Anthropogenic structures can alter ecosystem structure and functioning in many marine ecosystems but the responses on continental margins are poorly known. Here, we investigate the short-term response of benthic megafauna to the installation of a 56 km-long 30 cm diameter pipeline on the Angolan Margin (Block 31) from 700 to 1800 m water depth using remotely operated vehicle imagery. Clear depth-related patterns exist in the density, diversity and community structure of megafauna observed in 2013 prior to pipeline installation. These patterns are altered in a subsequent survey in 2014, three-months after pipeline installation. Significant increases in density, particularly in mid-slope regions are observed. Diversity is generally, but not consistently, enhanced, particularly in the shallower areas in 2014. Clear changes are noted in community structure between years. These changes are primarily caused by increases in the abundance of echinoderms, particularly the echinoid Phormosoma sp. indet. There was no evidence of colonisation of the pipeline in three months by visible fauna. The few large anemones observed attached to the pipe may be able to move as adults. The pipeline appeared to trap organic material and anthropogenic litter, and may enhance available food resources locally as well as providing hard substratum. These results indicate complex and ecosystem-dependent responses to structure installation and caution against simplistic approaches to environmental management.

Recommendations for the Standardisation of Open Taxonomic Nomenclature for Image-Based Identifications - Tammy Horton; Leigh Marsh; Brian J. Bett; Andrew R. Gates; Daniel O. B. Jones; Noëlie M. A. Benoist; Simone Pfeifer; Erik Simon-Lledó; Jennifer M. Durden; Leen Vandepitte; Ward Appeltans (Frontiers in Marine Science, 2021)
This paper recommends best practice for the use of open nomenclature (ON) signs applicable to image-based faunal analyses. It is one of numerous initiatives to improve biodiversity data input to improve the reliability of biological datasets and their utility in informing policy and management. Image-based faunal analyses are increasingly common but have limitations in the level of taxonomic precision that can be achieved, which varies among groups and imaging methods. This is particularly critical for deep-sea studies owing to the difficulties in reaching confident species-level identifications of unknown taxa. ON signs indicate a standard level of identification and improve clarity, precision and comparability of biodiversity data. Here we provide examples of recommended usage of these terms for input to online databases and preparation of morphospecies catalogues. Because the processes of identification differ when working with physical specimens and with images of the taxa, we build upon previously provided recommendations for specific use with image-based identifications.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Regulation of gvp genes encoding gas vesicle proteins in halophilic Archaea - Sandra Scheuch; Larissa Marschaus; Simone Sartorius-Neef; Felicitas Pfeifer (Archives of Microbiology, 2008)